2009
DOI: 10.1530/rep-09-0042
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposon expression as a defining event of genome reprograming in fertilized and cloned bovine embryos

Abstract: Genome reprograming is the ability of a nucleus to modify its epigenetic characteristics and gene expression pattern when placed in a new environment. Low efficiency of mammalian cloning is attributed to the incomplete and aberrant nature of genome reprograming after somatic cell nuclear transfer (SCNT) in oocytes. To date, the aspects of genome reprograming critical for full-term development after SCNT remain poorly understood. To identify the key elements of this process, changes in gene expression during ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
(41 reference statements)
2
39
0
Order By: Relevance
“…Genomic assembly of these ESTs and functional analyses through their knock down is underway. Our results showing that, in addition to protein encoding RNAs, mitochondrial RNAs and also lncRNAs are important component of the embryonic transcriptome corroborates results from Bui et al (2009). However, in this report, quantification of one of the retrotransposons at the morulae stage showed similar levels between in vitro fertilized and Figure 7 Pathway influenced by the presence of serum during either IVM or IVC (treatments 3 and 4).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Genomic assembly of these ESTs and functional analyses through their knock down is underway. Our results showing that, in addition to protein encoding RNAs, mitochondrial RNAs and also lncRNAs are important component of the embryonic transcriptome corroborates results from Bui et al (2009). However, in this report, quantification of one of the retrotransposons at the morulae stage showed similar levels between in vitro fertilized and Figure 7 Pathway influenced by the presence of serum during either IVM or IVC (treatments 3 and 4).…”
Section: Discussionsupporting
confidence: 88%
“…cloned from somatic cell nuclear transfer (SCNT) counterparts, which is indicative of normal reprogramming (Bui et al 2009). In contrast, we report in this study that the in vitro culture environment is influencing the level of expression of lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…6A). The reason for this replacement is not fully understood, but it has been reported that differential expression of transposable elements triggers sequential reprogramming on the embryonic genome (Peaston et al 2004;Bui et al 2009). First, by NGS and later confirmed by RT-qPCR, we detected high expression levels of mmur001272954 small RNA, which was classified as endosiRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, robust LTR retrotransposon up-regulation has been shown during activation of the bovine embryo genome [63] and found to be a general requirement for progression through to the cleavage stage in mouse embryos [64, 65]. However, the nature of its role in mammalian early development remains elusive.…”
Section: Discussionmentioning
confidence: 99%